Manufacturing of Hybridomas-Producers of Monoclonal Anti-Bodies to Tularemia Agent Antigens - O. O. Fomenkov; G. D. Elagin; G. V. Kuklina; D. V. Pechenkin; V. V. Krupin; N. V. Bogacheva; A. A. Kytmanov; A. V. Eremkin; O. V. Tikhvinskaya; E. Yu. Vakhnov (Проблемы особо опасных инфекций, 2015)
Carried out have been two experimental studies on hybridization of mouse myeloma cells and lymphocytes of BALB/c mice immunized with inactivated microbe Francisella tularensis cultures. As a result obtained have been hybridomas-producers of monoclonal antibodies (MAb) specific to the antigens of tularemia agent. Evaluated have been the prospects of its application for the detection of the agent under discussion using enzyme-linked immunoassay. Established is the fact that monoclonal antibodies produced by 31G1F10, 32E5D3, 35B11C8, 36C2F11 hybridomas make it possible to identify microbe cells of various tularemia agent strains when concentrated up to 0.5·106 mc/sm3, and do not interact with cultures of heterologous microorganisms when concentrated to 1.0·108 mc/sm3, which testifies to their specificity. These MAb are planned to be used for the construction of immune-enzyme and immune-chromatographic test-systems designed for tularemia agent detection.